2022
DOI: 10.1186/s12913-021-07461-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of acute care resource utilization among individuals with sickle cell disease in a middle-income country

Abstract: Background The costs associated with the treatment of sickle cell disease (SCD) are understudied in low and middle-income countries (LMIC). We evaluated the cost of treating SCD-related acute complications and the potential cost-savings of hydroxyurea in a specialized hematology center in Brazil. Methods The costs (US dollars) of emergency department (ED) and hospitalizations from SCD-related complications between 01.01.2018 and 06.30.2018 were asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The most common cause of ED visits among our SCD pediatric patients was acute painful crises among (73.91%) of patients. This result is similar to that reported by other researchers in different countries [ 10 , 19 , 22 ]. Initially, it was believed that the change in flow characteristics and erythrocyte aggregation alone caused vaso-occlusion and pain, however, the cause of vaso-occlusion is multifactorial.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most common cause of ED visits among our SCD pediatric patients was acute painful crises among (73.91%) of patients. This result is similar to that reported by other researchers in different countries [ 10 , 19 , 22 ]. Initially, it was believed that the change in flow characteristics and erythrocyte aggregation alone caused vaso-occlusion and pain, however, the cause of vaso-occlusion is multifactorial.…”
Section: Discussionsupporting
confidence: 93%
“…In Brazil, as a middle-income country, acute painful episodes were responsible for 64% of all visits to the ED with a median cost of $127.11/visit, followed by infections, exacerbation of anemia, and organ damage. Exacerbation of anemia was the most expensive cause of ED visits ($321.87/visit), followed by chronic organ damage ($236.40/visit) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, few studies have been published evaluating the financial and budgetary issues of the care line for chronic diseases. Lobo et al (2022) 22 studied the costs associated with the treatment of sickle cell disease (SCD) in low- and middle-income countries and reported that analgesics, antibiotics and housing were at the forefront of most expenses in SCD acute events. Hospitalization costs were higher among children, compared to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Economic burden related to several hematologic conditions were previously conducted in Brazil [ 20 , 46 50 ]. However, there are no studies using similar methods to estimate burden of illness in the country to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, only direct medical costs were included [ 18 , 19 ]. In Brazil, Lobo and colleagues (2022) reported emergency visits and hospitalizations total costs higher than USD 500,000 [ 20 ]. Nevertheless, only a single study, conducted in a single center, reporting direct costs is available to date.…”
Section: Introductionmentioning
confidence: 99%